2010
DOI: 10.1111/j.1537-2995.2010.02687.x
|View full text |Cite
|
Sign up to set email alerts
|

A functional AQP1 allele producing a Co(a–b–) phenotype revises and extends the Colton blood group system

Abstract: The Co(a-b-) phenotype can be generated by a functional AQP1 allele, that is, AQP1 140G encoding AQP1 (Q47R) and allowing the development of a novel Colton alloantibody. This study also shows that the Co(b) antigen can be produced by at least two different substitutions at Amino Acid Position 45, that is, A45V and A45T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Her antibody did not react with Co(a − b − ) cells, but could not be anti -Co3 as it did not react with her own Co:3 red cells [40] . Two other Co(a − b − ) individuals with the Gln47Arg are reported [40,41] . − 04 ).…”
Section: Co4 and The Co( A−b−) Co:3 Phenotypementioning
confidence: 98%
See 1 more Smart Citation
“…Her antibody did not react with Co(a − b − ) cells, but could not be anti -Co3 as it did not react with her own Co:3 red cells [40] . Two other Co(a − b − ) individuals with the Gln47Arg are reported [40,41] . − 04 ).…”
Section: Co4 and The Co( A−b−) Co:3 Phenotypementioning
confidence: 98%
“…Her phenotype was not Co null as her red cells expressed normal levels of Co3, normal quantities of AQP1, and exhibited normal water permeability. Transfection experiments in K562 cells demonstrated that Gln47 is also required for Co b expression [40] . She was homozygous for 140A > G encoding Gln47Arg ( CO * 01.…”
Section: Co4 and The Co( A−b−) Co:3 Phenotypementioning
confidence: 99%
“…The function of AQP-1 in RBCs may be to rehydrate rapidly after shrinking in the hypertonic environment of the renal medulla (Smith et al, 1993). Co a has a prevalence of 99.9%, its antithetical antigen Co b has a prevalence of 10%, and Co3 and Co4 are present on all RBCs except on those of the very rare Co(aÀbÀ) null phenotype (Arnaud et al, 2010). Apparently healthy individuals with the Co(aÀbÀ) phenotype and AQP-1 deficiency have RBCs with an 80% reduction in the ability to transport water.…”
Section: Colton Blood Group Systemmentioning
confidence: 99%
“…Molecular analysis of AQP1 revealed homozygosity for 140A>G, encoding the amino acid change Gln47Arg, in close proximity to the Co a /Co b polymorphism at residue 45. Samples from a second Co(a–b–) proband homozygous for the same 140A>G mutation were investigated following detection of an antibody to a high incidence antigen initially identified as anti-Co3 [15]. Unexpectedly, her RBCs were shown to have functional aquaporin 1.…”
Section: System 15: Comentioning
confidence: 99%
“…Expression studies with AQP1 encoding Arg47 demonstrated a loss of Co a antigen expression despite the presence of the Co a -specific Ala45, consistent with the observed phenotype. Arnaud and colleagues [15] also re-evaluated three antisera classified as anti-Co3 in their collection and re-identified one of the three sera as anti-Co4. PCR-RFLP analysis revealed that this sample also was homozygous for AQP1 140G.…”
Section: System 15: Comentioning
confidence: 99%